PREDIKSI KEBUTUHAN TENAGA KERJA DAN ANALISIS JABATAN SEBAGAI DASAR PERENCANAAN SUMBER DAYA MANUSIA - Arobi Zulkurnain; Riskika Velania Istiqomah; Nasya’a Nadyah Aisyah; Mardiyah Mardiyah (STKIP Pesisir Selatan, 2025)
The growing intensity of global competition requires organizations to implement strategic human resource (HR) planning to ensure sustainability and strengthen competitiveness. Workforce forecasting and job analysis are essential steps to guarantee the availability of employees who meet organizational needs in both quantity and quality. This study aims to examine the role of workforce forecasting and job analysis as the foundation of effective HR planning.This research applies a qualitative method with a library research approach. Data were obtained from books, scientific articles, and previous studies, then analyzed descriptively and analytically to provide comprehensive conceptual insights.The findings indicate that forecasting techniques such as Delphi, extrapolation, indexation, and statistical analysis help organizations anticipate risks of understaffing or overstaffing. Meanwhile, job analysis serves as a foundation for preparing job descriptions, job specifications, and job evaluations, which are crucial for recruitment, training, performance appraisal, and career development. The integration of workforce forecasting and job analysis provides a clear direction for HR planning, making it more efficient, measurable, and sustainable. Thus, the availability of competent and well-planned HR is a key determinant for organizations to adapt to changes and maintain long-term competitiveness.